Structural investigation of the interaction between glypican-3 and uncoordinated-5 - Akkermans, O (2019)
Uncoordinated-5 (Unc5) receptors are known for their function to induce repulsion in axonal and cell migration. Another proposed function is as dependency receptors where withdrawal of their ligands results in apoptosis. Unc5’s interactions with its ligands Netrin and fibronectin leucine-rich transmembrane (FLRT) have been extensively investigated; however, the molecular mechanisms of Unc5 as a switch for repulsive signalling and as a dependency receptor remain elusive. Recent work identified a novel interaction between Unc5 and Glypican-3 (GPC3), for which there are no known biological functions. GPC3 is a GPI-anchored heperan sulfate proteoglycan that has been studied in its role of modulating several morphogen signalling pathways. Using X-ray crystallography, this thesis reveals the structure of the core protein of human and mouse GPC3 at 2.6 and 2.9 Å resolution respectively. From this, the crystal structure of the GPC3/Unc5 complex was solved in two different crystal forms, at 4.0 to 4.6 Å. The crystal structure revealed an octameric assembly, showing that GPC3 clusters several Unc5 receptors. Biophysical studies attempted to validate the identified stiochiometry to further understand the molecular mechanisms of this interaction. The work presented provides the foundations for further functional studies for the GPC3/Unc5 interaction.